(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article describes the new procedure for financing the healthcare system of the republic, the scope of medical care provided based on a guaranteed package funded by the state budget, and the form of its financing. It examines the types of medical services included in this package, their quantity and conditions of use, as well as the medical institutions participating in the insurance system. The text highlights organizational issues, advantages and disadvantages of the implemented insurance system, the reasons for their occurrence, and ways to address the problems. Foreign experience in ensuring the effectiveness of medical institutions is also presented.